Pengaruh Kompensasi dan Pengembangan Karir Terhadap Kepuasan Kerja Karyawan - Mutiara Dhea Herliana; Munawaroh Munawaroh (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
This study aims to analyze and determine the effect of compensation and career development on employee job satisfaction, both partially and simultaneously. The population of this study were permanent employees of PT. Nikomas Gemilang, Serang Regency, Banten with a research sample of 100 people. This study uses primary data sources by distributing questionnaires in the form of a Likert scale. The data analysis technique used is multiple linear regression with the help of the SPSS version 25 program. The results of the study indicate that there is a positive and significant influence between compensation and career development on job satisfaction, both partially and simultaneously.